Improvements in saline soil and the law of water-salt transport based on salt inhibition using MICP technology - Xiaorong Wang; Chi Li; Yanru Shi; Zhenguo Zhang; Qingguo Chi; Panshi Wang (Biogeotechnics)
Soil desertification and salinization are the main environmental disasters in arid and semi-arid areas. It is of great significance to study the water - salt migration law of saline soil and propose corresponding water- salt regulation and control measures. Microbial-induced calcite precipitation (MICP) technology was proposed to improve saline soil based on salt inhibition, and the water–salt–heat coupling migration law and salt-frost heave deformation law of saline soil before and after improvement were studied using soil column model tests. XR1#, XR2#（Saline-alkali-tolerant mineralization bacteria isolated from saline soil) and Sporosarcina pasteurii were used in the MICP improvement and the effect of XR1# was the best. Under high-temperature evaporation, the water migration change rate, water loss rate, accumulated evaporation amount, and accumulated salt content of the improved soil columns within a depth range of 0–40 cm were reduced by an average of 53.6 %, 47.3 %, 69.5 %, and 40 %, respectively, compared with the untreated soil column. During low-temperature cooling, the characteristics of water-salt migration changed significantly, and the deformation of salt-frost heave decreased significantly. The water-salt content at the freezing point (−4.5 °C) changed from a cliff-like steep drop (untreated saline soil) to a slow decrease at environmental temperature (MICP-treated saline soil), and the amount of water crystallization decreased from 81 % to 56.7 % at −5 °C. At the end of the cooling process, the amount of salt-frost heaving on the surface of the soil columns decreased by an average of 62.7 %. Based on the measured data, a numerical simulation was conducted using the HYDRUS-1D model, which had good reliability and accurately simulated and predicted the law of water-salt migration in saline soil under the conditions of microbial solidification and improvement. MICP technology significantly reduced the change rate of water-salt migration and water evaporation in saline soil, hindered salt accumulation, and reduced salt-frost heave deformation, which effectively improved saline soil. The research results provide an important innovation and theoretical basis for the improvement of saline soil.